Predicting sample heating induced by cantilevers illuminated by intense light beams - Tremoço, Frederico (2022)
Funding Information: Ana I. Gómez Varela acknowledges support from the Xunta de Galicia, Consellería de Cultura, Educación e Ordenación Universitaria e da Consellería de Economía, and Emprego e Industria (postdoctoral contracts ED481D-2021-019 and ED481B 2017/103). Adelaide Miranda and Pieter A. A. De Beule acknowledge financial support from Norte's Regional Operational Programme 2014-2020-Norte2020 (NORTE-1-145-FEDER-19). This work was supported by the Fundação para a Ciência e a Tecnologia project SAM – [PTDC/NAN-OPT/31596/2017]. Publisher Copyright: © 2022